The Implementation of the K-Means Clustering Algorithm in Grouping Students Based on Learning Style Using Rapidminer - Saputra, Maulian; Saragih, Juliyandri; Susilawati (Bahasa Indonesia, 2023)
Learning style is an important factor that influences the effectiveness of individual learning. In this study, data on students' learning style preferences were collected and analyzed using the K-Means Clustering algorithm. The clustering results provide insights into different patterns of learning styles among students. This research assists educators in designing learning strategies that are more tailored to the individual needs of students, thereby enhancing the effectiveness of learning in the educational environment.